Estudo da atividade do Alcaloide Milonina, em modelos experimentais de inflamação aguda e dor - Silva, Larissa Rodrigues (2017)
Inflammation is an immune response that aims to establish a tissue homeostasis during an infection or injury. Recognized as a beneficial process, an inflammation can become harmful when in excess. Thus, therapeutic therapies that are applied to the resolution of the inflammation are studied and developed, with natural products and their derivatives playing a prominent role in the discoveries of new anti-inflammatory molecules. In this context, the objective of this study was to evaluate the antiinflammatory potential of milonine, a Cissampelos sympodialis Eichl alkaloid, in vivo, against the release of mediators by using the murine model of acute inflammation and pain. Swiss mice pretreated with milonine were submitted to protocols of: paw edema induced by LPS, prostaglandin (PGE2), bradykinin (BK) and serotonin (5-HT) to evaluate the anti-edematogenic activity of the alkaloid; microvascular permeability induced by acetic acid to obtain a total protein concentration and histological analysis of the peritoneum; the models of carrageenan-induced peritonitis to evaluate the effect of milonine on the migration of the total and differential cells; and the formalin test to evaluate its nociceptive activity. The results show that milonine was capable of significantly reduce (p<0.001) the formation of the paw edema induced by LPS, PGE2, BK, however it was not capable to reduce the edema induced by 5-HT; significantly reduced (p<0.05) the extravazation of liquid to the peritoneum induced by acetic acid, maintaining its morphology preserved. The alkaloid was also able to inhibit (p<0.01) the migration of the total leukocytes to the peritoneal cavity during the carrageenan-induced inflammation, decreasing the number of polymorphonuclear cells (PMN) without changing mononuclear cells (MNs). In the formalin test, the paw licking time of the animals was inhibited (p<0.01) only in the second phase through the intraperitoneal (i.p.) administration, corroborating the inhibition of inflammatory mediators. Therefore, this study demonstrates that milonine has an antiinflammatory and analgesic activity due to the inhibition of the action of mediators essential for the start of the inflammatory process.